Therapeutic synergy between swimming and photobiomodulation in a rat model of neuropathic pain - Araujo, Luara Caniato; Silva, Danielle P. F. B.; Rocha-Braga, Lara Caetano [UNESP]; Ciena, Adriano Polican [UNESP]; Chacur, Marucia (Springer Nature, 2025)
This study aimed to evaluate the efficacy of non-pharmacological interventions, photobiomodulation therapy (PBMT) and swimming (SW), administered individually or in combination, in alleviating neuropathic pain, enhancing motor function, and preserving skeletal muscle morphology in a rat model of chronic constriction injury (CCI) of the sciatic nerve. Male Wistar rats (n = 8 per group) with chronic constriction injury (CCI)-induced neuropathic pain were randomly assigned to receive photobiomodulation therapy (PBMT), swimming exercise (SW), a combination of both therapies, or no treatment (control). The treatment protocol lasted for 3 weeks, with PBMT applied at a dose of 6 J/cm² (wavelength 904 nm) delivered to the affected limb, and swimming sessions conducted 10–30 min per day, 5 days per week. Behavioral assessments, including mechanical hyperalgesia (Von Frey test), thermal hyperalgesia (Hargreaves test), cold allodynia, and motor function (incapacitance test) were performed weekly to evaluate nociceptive thresholds and functional recovery. Histological analyses of the gastrocnemius muscle were conducted post-treatment to assess morphometric changes, including myofiber integrity, central nucleation, and collagen distribution using PicroSirius Red staining. Both PBMT and SW significantly reduced mechanical and thermal hypersensitivity and improved motor performance compared to untreated CCI rats (p < 0.05). The combination therapy demonstrated superior analgesic and functional outcomes relative to monotherapies (p < 0.01). Histological analysis revealed a reduction in centrally located nuclei and increased collagen expression in treated groups, with the combined intervention showing the most pronounced improvements. PBMT and swimming exercise independently alleviate neuropathic pain and mitigate muscle degeneration following sciatic nerve injury. When combined, these therapies produce additive or synergistic effects, supporting the implementation of multimodal, non-pharmacologic strategies for managing neuropathic pain and promoting functional recovery.